Diagnosis of female sexual dysfunction - adaptation test - Stefankiewicz, Małgorzata; Ślaski, Sławomir (Studia Psychologica: Theoria et praxis, 2010)
The main problem of this paper is to present an adaptive procedurę for Sexual Functioning Questionnaire, which was used in Polish conditions. The results obtained in validation studies of the Polish population, which is different culturally can be considered as similar.